Transition-Metal-Free Alkynylation of Aryl Chlorides - Truong, Thanh (2011)
[Image: see text] Two sets of conditions have been developed for a base-mediated, transition-metal-free alkynylation of aryl chlorides that proceeds via benzyne intermediates. The first set of conditions involves the use of TMPLi base in a pentane/THF mixture at 25 °C. The second set involves use of a metal alkoxide base in dioxane at elevated temperature. Reasonable functional group tolerance has been observed. Fluoro, trifluoromethyl, silyl, cyano, and alcohol functionalities are compatible with the reaction conditions.